Література у світі постправди - Поліщук, Я. (Слово і Час, 2020)
У статті розглянуто актуальний стан літератури, яку маргіналізував бум сучасних мас-медіа та вільний ринок. Три аспекти постмодерного світогляду — дегуманізація мистецтва, деієрархізація та множинність правди, утрата харизми автора — зумовили тривалу кризу
в пострадянських літературах, однак у ширшому контексті також
у суспільних відносинах та громадській думці. Продовження цієї кризи забезпечує застосування технологій, спрямованих на продукування
постправди. У сучасному світі література не є вповні відповідальною за кризовий стан суспільства, проте її причетність до цього явища
безумовна. Автор статті аналізує приклади заангажованості літератури в ідеологічні конфлікти та в пропагандистську риторику.
Спостереження за новинками російської, української та білоруської
літератур дає добрий матеріал для дослідження постправди в їхній східноєвропейській модифікації. The author examines the current state of literature, which has been marginalized by the
boom of modern media and the free market. Literature is called to restore a worthy place
in the system of cultural communication of society. It is contradicted by the experience of
postmodernism, which has led to disorientation in the system of art values. Postmodernism was an important formation of the transition period. Three aspects of the postmodern
worldview — dehumanization of art, lack of truths’ hierarchy and their plurality, and the
loss of the author’s authority — have led to a long-lasting crisis in the post-Soviet literatures,
but in the wider context, it was a crisis of relations with society and public opinion. The continuation
of this crisis is stimulated by the use of technologies aimed at producing the posttruth.
In the contemporary world, dominated by mass media and popular culture, fiction
is not fully responsible for the crisis of society. The author of the paper considers examples
that confirm the relevance of literature to ideological conflicts and propaganda rhetoric. The
novelties of Ukrainian, Russian, and Belarusian literatures provide good material for the
study of the post-truth in its Eastern European modifications. Nowadays fiction is seeking
its place once again; its potential means of influencing the human consciousness in the posttruth
world are being renewed. This process should be seen dialectically, with its probable
positive and negative consequences. The post-truth world gives literature a chance to leave
the shadows of media and restore its authority in the cultural sphere. At the same time, the
confluence of literary fiction with post-truth poses a considerable danger, since it may be applied
in modern manipulative technologies. The establishment of social and psychological
communication, which became one of the priority tasks of modern literature, should not be
implemented at the cost of human degradation.